2017
DOI: 10.1093/mnras/stx2727
|View full text |Cite
|
Sign up to set email alerts
|

Probing the local environment of the supernova remnant HESS J1731−347 with CO and CS observations

Abstract: The shell-type supernova remnant HESS J1731−347 emits TeV gamma-rays, and is a key object for the study of the cosmic ray acceleration potential of supernova remnants. We use 0.5-1 arcminute Mopra CO/CS(1-0) data in conjunction with HI data to calculate column densities towards the HESS J1731−347 region. We trace gas within at least four Galactic arms, typically tracing total (atomic+molecular) line-of-sight H column densities of 2-3×10 22 cm −2 . Assuming standard X-factor values and that most of the HI/CO em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 75 publications
(123 reference statements)
0
26
0
Order By: Relevance
“…In our model it represents the entire space other than the MC-clumps -MC-core and MC-J1729. (Maxted et al 2018), and the TeV image by Abramowski et al (2011) is shown in green contours. The color bar represents the scale of CO line intensity with a unit of K km s −1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our model it represents the entire space other than the MC-clumps -MC-core and MC-J1729. (Maxted et al 2018), and the TeV image by Abramowski et al (2011) is shown in green contours. The color bar represents the scale of CO line intensity with a unit of K km s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…These features can be seen clearer in Fig. 2 of Maxted et al (2018), due to a different scale of color bar used in their CO map.…”
Section: Nearby Molecular Cloudsmentioning
confidence: 96%
See 2 more Smart Citations
“…However, evidence for a dominant hadronic component for HESS J1731−347 only exists for the 5.2-6 kpc distance solution, as opposed to the 3.2 kpc solution favoured by theCui et al (2016) model and explicitly derived inMaxted et al (2018a) …”
mentioning
confidence: 85%